1983
DOI: 10.1111/j.1423-0410.1983.tb04490.x
|View full text |Cite
|
Sign up to set email alerts
|

A Caucasian Family with the i Phenotype and Congenital Cataracts

Abstract: Abstract. A three‐generation consanguineous Caucasian family in which 2 siblings have autosomal recessive cataracts and the phenotype I negative, i positive is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The association does not seem to be as pronounced in the white population, however, with only 3 individuals in 2 families formally reported as having both the adult i phenotype and congenital cataracts. [24][25][26] The association of the adult i phenotype with congenital cataracts can be explained either by a close linkage between independent I-and cataract-related genes or by a pleiotropic effect of the gene responsible for the adult i phenotype on the development of cataracts. However, because of the reduced strength of the association in whites, it has been suggested that the former hypothesis of a close linkage between 2 independent genes is the more tenable one.…”
Section: Introductionmentioning
confidence: 99%
“…The association does not seem to be as pronounced in the white population, however, with only 3 individuals in 2 families formally reported as having both the adult i phenotype and congenital cataracts. [24][25][26] The association of the adult i phenotype with congenital cataracts can be explained either by a close linkage between independent I-and cataract-related genes or by a pleiotropic effect of the gene responsible for the adult i phenotype on the development of cataracts. However, because of the reduced strength of the association in whites, it has been suggested that the former hypothesis of a close linkage between 2 independent genes is the more tenable one.…”
Section: Introductionmentioning
confidence: 99%
“…Autosomal recessive inheritance of congenital cataracts is rare, although there have been some cases reported (Francois et al 1982;Macdonald et al 1983;Shokeir and Lowry 1985;Forsius et al 1992;Ippel et al 1994). Yamagucho presented evidence suggesting the linkage of Iiblood group located at 9q21 (Bierhuizen et al 1993) with a recessive form of congenital cataracts, and this linkage was confirmed later by Ogata et al (1979).…”
Section: Genetic Linkage Of Congenital Cataractsmentioning
confidence: 92%
“…2,11 In certain kindreds, i adult is associated with congenital cataracts. [12][13][14] Based on older serologic studies, the incidence of i adult ranges from 1 in 4400 to 1 in 17,000. 1,15 The prevalence of mutant IGnT alleles in the general population is unknown but is presumably rare.…”
Section: Systemmentioning
confidence: 99%
“…Subsequent studies by other investigators, however, were conflicting, indicating that the i adult phenotype did not always predispose to congenital cataracts, particularly in non-Asian populations. 13,14 The apparent discrepancy was finally resolved with cloning of the IGnT gene, 38 followed by sequencing analysis of i adult individuals. 7-10 As already described, the i adult phenotype without cataracts is the consequence of mutations affecting exon E1C, leading to an isolated loss of IGnT activity in erythroid cells (Table 2, Fig.…”
Section: Cataractsmentioning
confidence: 99%